Degradasi Congo Red Secara Fotosonolisis Menggunakan Katalis ZnO-TiO2 - Amelia, Reza; Sanjaya, Hary (Periodic, 2019)
This study aims to determine the optimum time and amount of TiO2 used for doping the optimum ZnO in degrading Congo Red dye. The results of the percentage degradation were obtained from the absorbance value which was measured using a UV-Vis Spectrophotometer. (Î»max) Congo Red obtained from measurements using a UV-Vis Spectrophotometer is 498 nm. The results showed that the optimum irradiation and sonication time to degrade Congo Red was 75 minutes with a degradation percentage of 98.11%. On the effect of variations in the amount of TiO2 doping showed optimum results at 20% ZnO-TiO2, with a degradation percentage of 96.85%. The results of XRD analysis showed that the crystal size of 20% ZnO-TiO2 was 48.57-96.58 nm. While analysis with UV-DRS obtained a band gap value of 20% ZnO-TiO2 which is 3.11 Ev.